Gender Equality and Women's Empowerment Between Expectations and Reality in Small Cities - Cahyani, Cahyani; Anez, Celbi; Billa, Putri Salsa; Siswoyo, Mukarto; Khumayah, Siti (Devotion : Journal of Research and Community Service, 2024)
One of the successes of development is that the role of men and women is very influential on the success of development. In this case, the Cirebon City government issued Regional Regulation Number 7 of 2021 concerning the Regional Medium Term Government Plan, namely "In creating a society with human resources that are competitive and superior in all fields". This observation aims to find out implementation policies and expectations in the gender mainstreaming program. in realizing gender equality, what is the reality in the Cirebon City Community, then what are the supporting and inhibiting factors, in an effort to overcome policy obstacles to implementing gender mainstreaming programs in DP3APPKB in Cirebon City. This research uses a descriptive qualitative method using primary techniques, namely from in-depth interviews consisting of the DP3APPKB Gender Mainstreaming Sub-Coordination and the Cirebon City Community. Secondary data has been obtained from documentation and archives at DP3APPKB as well as several statutory regulations and other documents that support this research. George C Edwards' theory used in this research covers the success of policy implementation which is influenced by four aspects, namely: Communication, Resources, Disposition or Attitude of the Implementer and Bureaucratic Structure. The results of this research show that the implementation of the gender mainstreaming program has been quite successful, but there is still a lack of response from the community and an uncertain budget from the government so that it is less than optimal for realizing gender equality in the development sector in Cirebon City.